Complementary Learning: When Virtual Reality Meets Anthropology - Ida Lestari Harahap; Arfi Syamsun; Pujiarohman Pujiarohman; Lenny Herlina; Muhammad Fikriansyah; Giri Wahyu Wiriasto (Postgraduate, University of Mataram, 2025)
The foundation of anthropology learning lies in the knowledge of the human skeletal system. As human skeletons have become increasingly difficult to obtain, complementary anatomy learning tools are needed. One innovation that can enhance students’ understanding of anatomy is the use of three-dimensional technology through virtual reality (VR). The use of VR in learning is expected to help students study anatomical structures in greater detail compared to relying solely on atlases or textbooks. This study employed a cross-sectional design involving 22 first-semester medical students from the Faculty of Medicine and Health Sciences, University of Mataram (FKIK Unram), focusing on osteology anatomy. Students were given the opportunity to study the skeletal system using the Oculus Quest 3 virtual reality device. The skeletal framework within the VR application was specifically designed for medical students, featuring Latin bone labels and adjusted to the undergraduate competency level. The study also evaluated students’ expectations, which were generally categorized as high, with a mean score of 4.18. Only one item was categorized as moderate, with a mean score of 4.00, likely due to the short duration of VR exposure. Overall, students demonstrated high acceptance and expectations toward the use of virtual reality as a complementary tool in anatomy learning.